Sixteen-years Application of Organic Manures and Fertilizers in Pearl Millet–Wheat Cropping System on Soil Fertility and Soil Carbon Management Index in an Inceptisol of Subtropical India - B.H. Kumara (Journal of the Indian Society of Soil Science, 2022)
A study was undertaken in a long-term experiment on effect of organic manures and nutrient management on soil fertility and soil organic carbon (SOC) after 16 years cycles of pearl millet–wheat cropping system in a coarse loamy, Typic Haplusterts of subtropical India. Significant build-up of soil fertility in terms of alkaline KMnO4-N, Olsen-P, NH4OAc-K as well as SOC namely, total organic carbon (TOC), Walkley and Black organic carbon (WBC), labile organic carbon (LBC) and periodical changes of SOC during cropping season were maintained under different organic manures (FYM, poultry manure and pressmud) alone or integrated nutrient management over control plot in different depths (0-15, 15-30 and 30-45 cm) of the soils. The highest values of TOC (13.2 g kg-1), WBC (11.2 g kg-1) and LBC (1.22 g kg-1) were maintained in 15 t FYM + 150 kg N ha-1 + 30 kg P2O5 ha-1 treated plot. The magnitude of change in WBC in subsurface (15–30 and 30-45 cm) soil was low compared to surface soil (0-15 cm). Highly strong relationships were exhibited between LBC with yield, indicating that these pools are more important for nutrient turnover and their availability to plants than total SOC. Carbon management index revealed that integrated nutrient management could be followed for enhancement of crop productivity, nutrient availability and soil carbon pools for long-term. These results conclude that for sustainable crop production and maintaining soil quality, input of organic manure like FYM is of major importance and should be advocated in the nutrient management of intensive cropping system for improving soil fertility and biological properties of soils.